505. Bezlotoxumab Reduces Recurrence of Clostridium difficile Infection in Immunocompromised Patients: Early Experience at a Tertiary Care Center. (26th November 2018) - Askar, Sally; Kenney, Rachel M; Conner, Ruth; Ramesh, Mayur; Alangaden, George
Abstract: Background: Bezlotoxumab (BEZ) was approved in 2017 for prevention of recurrent C. difficile infection (CDI), with a number needed to treat (NNT) of 10 reported in the registration trials. Little information is available on its effectiveness in high-risk populations. BEZ was added to the institutional outpatient formulary in 2017 for use in patients with CDI at high-risk for recurrent CDI (rCDI), i.e., history of solid organ (SOT) or hematopoietic stem cell (HCT) transplantation, active malignancy, chronic steroid (prednisone equivalent 20 mg/day), and failed fecal microbiome transplant (FMT). Patients that met criteria were referred by the antimicrobial stewardship team to the infectious disease clinic for BEZ insurance approval and administration. The goal of this study was to evaluate the effectiveness and safety of BEZ in this high-risk population. Methods: The cohort of patients referred for BEZ were compared by those who received BEZ vs. those who did not receive BEZ (standard of care, SOC). The primary endpoint was rCDI at ≤100 days of BEZ infusion or end-of-treatment (EOT). Secondary endpoints were time to rCDI and insurance status. Safety of BEZ was evaluated as infusion reaction ≤24 hours and death ≤100 days. Results: Twenty-nine patients were referred for BEZ; 14 (48%) received BEZ. Patient characteristics are in Table 1. rCDI at 100 days occurred in 14.3% BEZ vs. 28.6% SOC ( P = 0.3654) with an NNT of 7. Average time to rCDI was longer in the BEZ group vs. SOC (49 vs. 27 days). No infusion reactions or death were noted in the BEZ group. Insurance approval for BEZ was denied in 26.7%. Medicaid coverage was common in SOC (46.7% vs. 7.1%; P = 0.0191) and Medicare coverage was more common in BEZ group (71.4% vs. 33.3%; P = 0.0438). Conclusion: Early experience with BEZ appears promising in a high-risk, predominantly immunocompromised population. The NNT to prevent rCDI was 7. Larger cost–benefit studies in immunocompromised and transplant populations are warranted. Disclosures: All authors: No reported disclosures.